Tool Study #1 – Audiovisual interface, performance - Lapov, Anton (Revista Vórtex, 2021)
Musical work for the Dossier "A quarter of century of Pd: past, present and future" [note by editor] Link #1: https://youtube.com/playlist?list=PLXdYuKtwUhUrirWQ0B2X7XhfrBCGJVlGn